CONSUMPTION BEHAVIOR OF BIDIKMISI SCHOLARSHIP STUDENTS WITH RELIGIOSITY AS A MODERATING VARIABLE - Yafiz, Muhammad; Harahap, Isnaini; Cahyanti, Sri (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
A person's consumption depends on the amount of income earned. If a person's income increases, then consumption will also increase. Conversely, if income decreases, then consumption will also decrease. This study aims to analyze the influence of income, lifestyle, and social environment variables on student consumption behavior with religiosity as a moderating variable. The research method used is a quantitative method using anaccidental sampling technique. The data analysis technique applied is the Moderated Regression Analysis (MRA) test of SPSS 19.0. The results show that income has a positive and significant effect on student consumption behavior by 29.8%, lifestyle has a positive and significant impact on student consumption behavior by 27.6%, and social environment has a positive and significant effect on student consumption behavior by 24.1%. Income, lifestyle, and social environment simultaneously have a positive and significant impact on student consumption behavior with a significance value obtained reaches 0.000 <0.05, and Fcount is greater than Ftable (26.398> 2.47). Religiosity has a significant impact on consumption behavior with a significance value obtained of 0.036 <0.05, and tcount is greater than ttable (2.123> 1.985). Religiosity does not strengthen income, lifestyle, and social environment against consumption behavior. Income, lifestyle, and social environment have a positive effect on student consumption behavior with a moderate level of religiosity. In addition, religiosity affects consumption behavior, therefore it can be concluded that religious knowledge or ideology can influence consumers in choosing goods to consume, based on the value they believe in.